Determination of clamping force in high-tension bolts using ultrasonic method - Mahendra a/l Ramachandran (2023)
The primary aim of this paper is to dwell into the determination of clamping force in high-tension bolts through the adoption of the ultrasonic method. The sample was prepared using the ultrasonic method. There are 2 different materials namely Grade 8.8 and SS 304 tested with this method.